A relação entre benefícios simbólicos do consumo e identidade: uma investigação através de uma abordagem metodológica mista - Ferla, Diego Alexsander (Universidade do Vale do Rio do Sinos, 2008)
Consumption has been appointed as the fundamental pillar in the consumers’ identity formation. In areas such as sociology, psychology and anthropology, the idea of identity has been long discussed. Regarding consumer behavior, identity has been gaining notoriety in the last two decades. Since then, several studies about identity and consumption have been made. However, these studies had a qualitative characteristic, leaving a latent methodological gap. The purpose of this study is to verify the actual relationship between the symbolic benefits provided by consumption and the identity formation of young consumers through a theoretical multidisciplinary approach and of a mixed methodological approach which bring contribution, especially to the perspective of the consumer behavior. In the qualitative step of the study, in depth interviews and the auto driving technique have been used to identify the symbolic benefits perceived by the young consumers and to the elaboration of the questionnaire used in the quant
Keywords: benefícios simbólicos; consumo; identidade; jovens; consumidor; consumption; identity; youngster; symbolic benefits; Ciências Sociais Aplicadas